The segregation of educated youth and dynamic geographies of studentification. Issue 1 (7th January 2014) - Smith, Darren P; Hubbard, Phil
<x xml:space="preserve">Abstract</x> This paper explores how university students are enmeshed in the trend of increasing sociospatial segregation. The paper charts the unprecedented in‐migration of students into selected towns and cities as part of the expansion of UK higher education in the mid‐1990s, epitomised by single people living in multi‐person shared private rented housing, often alongside established households in socially‐mixed neighbourhoods. It is shown that student populations became more spatially concentrated during mid‐2000s with the development of purpose‐built accommodation, predominantly in the form of gated 'student‐enclaves'. We argue that these exclusionary, 'student‐only' spaces are becoming more widespread due to concurrent trends in the commodification of student housing and studenthood, which are encouraging the formation of 'new frontiers of student segregation'. The paper ends by discussing these trends, arguing for further research exploring the variegated spatial outcomes of these processes of segregation.